The origins and diversity of axial age civilizations - Aizenshṭadṭ, Shemuʾel Noaḥ (SUNY series in Near Eastern studies, 1986)
Introduction: The axial age breakthroughs -- their characteristics and origins / S.N. Eisenstadt -- The emergence of second-order thinking in classical Greece / Yehuda Elkana -- The emergence of an autonomous intelligence among the Greeks / Christian Meier -- Dynamics of the Greek breakthrough: the dialogue between philosophy and religion / S.C. Humphreys -- The meaning of the word [body] in the axial age: an interpretation of Plato's Cratylus 400C / R. Ferwerda -- The axial age breakthrough in ancient Israel / S.N. Eisenstadt -- Myth and reality in ancient Israel / Benjamin Uffenheimer -- The protest against imperialism in ancient Israelite prophecy / Moshe Weinfeld -- On self-consciousness in Mesopotamia / Peter Machinist -- Monarchy and the elite in Assyria and Babylonia: the question of royal accountability / Hayim Tadmor -- Eschatology, remythologization, and cosmic aporia / Michael E. Stone -- Old wine and new bottles: on patristic soteriology and Rabbinic Judaism / Gredaliahu G. Stroumsa -- The role of Christianity in the depolitization of the Roman Empire / Hans G. Kippenberg -- Architects of competing transcendental visions in late antiquity / G.W. Bowersock -- Historical conditions of the emergence and crystallization of the Confucian System / Cho-Yun Hsu -- Was there a transcendental breakthrough in China? / Mark Elvin -- The structure and function of the Confucian intellectual in Ancient China / Tu Wei-Ming -- The historical background of India's Axial Age / Hermann Kulke -- Ritual, revelation, and the Axial Age / J.C. Heesterman -- Aśvatthāman and Bṛhannaḍā: Brahmin and Kingly Paradigms in the Sanskrit epic / David Shulman -- Some observations on the place of intellectuals in Max Weber's sociology, with special reference to Hinduism / Edward Shils -- The reflexive and institutional achievements of early Buddhism / Stanley J. Tambiah -- The emergence of Islamic civilisation / Michael Cook.